Hyperoxy as a form of anaerobic workload reduction on the elite basketball players - Pupis, M.; Rakovic, A.; Savanovic, V.; Stankovic, D.; Kocic, M.; Beric, D. (Acta Kinesiologica, 2010)
In our research we were monitoring reaction of the body of basketball players on the inhalation of oxygen concentrate of 99.5 %. We were testing sportsmen on treadmill and on specific basketball test - Jugo test. Our research showed that after inhalation of oxygen players had lower lactate level (after third time). We didn`t find significant evidence that inhalation had positive effect on basketball players shooting. Result of our research is that inhalation of 99, 5% oxygen has positive effect during anaerobic loading in sport.